“MONITORING AND OPTIMIZING VISUAL LEARNING MATERIALS USING ARTIFICIAL INTELLIGENCE IN EDUCATION” - Qudratov Hasanali Otabek o‘g‘li (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article explores the use of Artificial Intelligence (AI) for monitoring and optimizing visual learning materials in educational settings. AI technologies enable educators to analyze student interactions, assess the effectiveness of visual resources, and adapt instructional content to enhance comprehension and engagement. The study highlights the pedagogical benefits of AI-driven monitoring, including real-time feedback, personalized learning pathways, and data-driven instructional improvements. Practical strategies for integrating AI to optimize visual learning materials are also discussed.